The dynamic anthropology in a perspective of the bioelectronics - Sedlak, Włodzimierz (Anthropological Review, 1980)
The author states that modern biology has reached a submolecular level of its insights and interests. Therefore this level, at which functional properties are described by physics of elementary particles, must be taken into consideration when dealing with man — especially with a problem of origin of his intellectual powers and consciousness.